The Fine Arts Learning of Free Expression As Children's Creativity Space: A Case Study At MI Alam Gaharu Baleendah School Bandung - Sahal, Muhammad; Wadio, Wadio; Na:am, Muh Fakhrihun (Universitas Negeri Semarang, 2021)
Making children's experiences during the implementation of learning as the center of the best approach in guarding learning activities is a form of Experiential learning method application, namely by making the students get the hands-on experience and carry out all teaching and learning activities practically in the field. Knowledge results from a combination of understanding and transforming experience (Kolb, 1984). Experiential learning focuses on the learning process of each individual. It is a student-centered approach that begins with the premise that people learn best from their experience. As revealed by Garha (1980: 60), the method of artistic expression is a method that gives children the freedom to be able to express their feelings without being limited by conventional rules or norms of creativity in making drawings, there is no domination of teachers in its practice, and teachers/facilitator only directs the students. The elementary school period is a golden age for developing all students' abilities, one of which is creative expression. This research focused on students' creativity in making artwork in the form of performance tests, which are seen from the idea of ​​creating (cognitive aspects), performance (psychomotor aspects), and work results (product aspects). This research was qualitative. In order to understand the various aspects and objectives of learning the Artistic Expression, the researchers used data collection techniques in the form of interviews, observations, and document studies. Seperti yang diungkapkan oleh Garha (1980: 60) bahwa Metode ekspresi bebas merupakan metode yang memberi keleluasaan kepada anak-anak untuk dapat menyalurkan ungkapan perasaan tanpa dibatasi oleh aturan-aturan atau norma cipta konvensional dalam membuat gambar, pada pelaksanaannya tidak ada dominasi guru, guru/ fasilitator hanya mengarahkan siswanya. Masa sekolah dasar merupakan masa keemasan berkembangnya seluruh berkemampuan siswa, salah satunya berekspresi kreatif. penelitian ini, memfokuskan pada kreativitas siswa dalam membuat hasil karya berupa tes unjuk kerja, yang dilihat dari ide pembuatan (aspek kognitif), kinerja (aspek psikomotor), dan hasil karya (aspek produk). Penelitian ini merupakan penelitian kualitatif. Guna memahami berbagai aspek dan tujuan pembelajaran Seni Rupa Ekspresi Bebas, peneliti menggunakan teknik pengumpulan data berupa wawancara, observasi dan studi dokumen.